Factibilidad y desarrollo de un Módulo de Crianza de Codornices en Tarapoto-San Martín - Saavedra Leiva, Juan Luis (2002)
In the years •98 and 99' the Region San Martín crossed a strong campaign for the upbringing and Production of eggs of Quail; being in those •years investment souce for the person that decided to be devoted to his upbringing. When lapsing the yeras tye demand of quail eggs in the region it has been sustained in fragile bases that have given place to that the mícroempresarios of quail egg goes shrinkíng their production seeing this wat in the same one the negatividad of the upbringing. Nevertheless the National University of San Martín to the vanguard of the scientific and technological developmet in the Region, Through the Ability of Agrarian Sciences seeks to demostreate the true benefits and possibilities of the Upbringing in San Martín. "Feasibility and Development of a I Modulate of Upbringíng of Quails in the area of the Huallaga and Low May of the Region San Martín" that had as time of realization the periods 2000 -2001 he/she has líke one of their fundamental objectives the one of settling down a I modulate of quailis in the I Found Miraflores Distrito of the Band of Shilcayo of the County and Region San Martín with the purpose of impelling the investigation as well as the corresponding technological and Scientific trasferencia to the Populations service San Martinense. The quail Cotumix cotumix japónica is one of the varieties but maids at National and international level showing adaptation and resistance to high temperatures as well as to diverse hight. In the Perú this variety for ist great wildness has shown tempting posture levels that you/they invite to the upbringíng of the same one. Keeping iin mind the necessitíes and requirements for the upbringíng of the quail to be devoted to their exploitation you determines the feasbility of upbringiing iin the Region San Martín showing this way an average of net entrance of 49 annual % of the total of the net sales; without lleaving asíde iit lleaves that; joined to the technical knowledge it is sought to conquer and to start a new source of revenues for the development of the Region.